Persuasion and Engagement in the Spanish Bookfluencers - Magadán Díaz, Marta; Rivas García, Jesús Israel (Publishing Research Quarterly, 2023)
This research aims to analyze the persuasiveness of bookfluencers and the impact of content formats on their followers’ engagement and intention to purchase books. The theoretical framework for this study is the Elaboration Probability Model (ELM) adapted to social networks. The research used the Experimental Vignette Methodology (EVM) through a questionnaire launched to users of YouTube, Instagram, TikTok, and via email to UEMC (Miguel de Cervantes European University) students. The data collected were treated statistically. The findings confirm the importance of argument quality in persuasive messages. The results highlight the significance of the audiovisual content format, both in the engagement and purchase intention, when followers process information through their central route.
Keywords: book; bookfluencer; engagement; persuasion; Spain; Scopus; Emerging